2018
DOI: 10.1080/01942638.2018.1505801
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a 5-Day Virtual-Reality Based Exercise Program on Kinematics and Postural Muscle Activity in Youth with Cerebral Palsy

Abstract: The effects of a 5-day virtual-reality based exercise programme on kinematics and postural muscle activity in youth with cerebral palsy ABSTRACT Aims: To determine the effects of a 5-day virtual reality (VR)-based intervention on anticipatory and reactive mechanisms of postural control in children and adolescents with cerebral palsy (CP). Methods: Eleven youth with CP (GMFCS levels I and II), ages 7 to 17, were allocated to intervention (N=5) and control (N=6) groups. Both groups attended balance assessment se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The findings indicated that 8-weeks CBFAE improved gross motor functions, walking distance and QoL of CP children. These findings substantiate the submission on exercise regimen being the most effective interventions for CP management ( 1 , 2 , 3 ). Specifically, with effects of 8-weeks CBFAE on gross motor functions of standing, walking, running and jumping, there was significant improvement.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings indicated that 8-weeks CBFAE improved gross motor functions, walking distance and QoL of CP children. These findings substantiate the submission on exercise regimen being the most effective interventions for CP management ( 1 , 2 , 3 ). Specifically, with effects of 8-weeks CBFAE on gross motor functions of standing, walking, running and jumping, there was significant improvement.…”
Section: Discussionsupporting
confidence: 82%
“…Cerebral palsy (CP) is a permanent but non-progressive damage to developing brain leading to permanent voluntary motor control and movement disorders in one or more limbs and sometimes in the trunk ( 1 , 2 , 3 ). CP commonly contributes to motor disability and serves as principal cause of physical disabilities in children ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…(3) articles which did not use VR exercise (e.g., some focused on VR only or VR exposure therapy (VRET) or Virtual Reality in Psychological Treatment (VRT)). The characteristics of the included studies are shown in the Table 2, which includes 11 RCTs [7,[21][22][23][24][25][26][27]30,32,34], three controlled trials [28,31,33] and one causal-comparative study [29]. In detail, all 11 RCTs used baseline and post-test results from the intervention and control groups as the basis of their conclusions [7,[21][22][23][24][25][26][27]30,32,34].…”
Section: Study Selectionmentioning
confidence: 99%
“…In detail, all 11 RCTs used baseline and post-test results from the intervention and control groups as the basis of their conclusions [7,[21][22][23][24][25][26][27]30,32,34]. Moreover, the three controlled trials compared the inferential statistics at baseline and post-test of the predetermined control and experimental groups [28,31,33]. Lastly, the causal-comparative study analyzed differences between the control group and the experimental group [29].…”
Section: Study Selectionmentioning
confidence: 99%
“…They concluded that also future studies needed to determine the most appropriate and effective game choices in Nintendo Wii Fit and integration with conventional therapy [31]. In recent research studies support the use of full-body movement VR-based exercise avaliable intervention to improve functional balance and mobility outcomes in children with CP [32][33][34]. In a study Mills et al found that there was no effect of a 5 day VR-based training on anticipatory or reactive postural control mechanisms used in response to oscillating platform perturbations in children with CP.…”
Section: Copy Right@ Tülay Tarsuslu şImşekmentioning
confidence: 99%